Work, dignity and visibility: allocating people with disabilities in the framework of public services as means to induce the implementation of inclusive public polices - Martins Teixeira, Bruno; Lôbo, Edilene (Revista da Faculdade de Direito do Sul de Minas, 2019)
This paper analyzes the social implications of the absence of people with disabilities in key public positions in the Brazilian labor market, as well as the effects of this in the feedback of prejudice and social exclusion in relation to this vulnerable group. In order to do so, a sample of the results of some of the most recent major public careers entrance exams in Brazil, for the positions of Judge, Prosecutor and Professor, have been drawn up in order to examine, in practice, the idea of broad accessibility to key positions, as proposed by the 1988 Constitution. Under the theoretical framework of the right to equality, and using the deductive method and bibliographical research, the conclusions point to the need for more investments in the implementation of accessibility and inclusive education resources, with the establishment of new affirmative measures aimed specifically at the promotion of labor inclusion in relation to the functions of greater responsibility within the public service.